Observations on The Life Cycle of An Eimeria SP.Of Chikens In Peninsular Malaysia - Budihardjo Budihardjo (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1975)
The life cycle of an unidentified Eimeria sp. from domestic chickens in Malaysia was studied. Sporulation of oocysts was completed in 34 hours at room temperature (30Â° C). Oocysts are ellipsoidal to ovoid averaging 21 by 18 millimicron with a yellowish double waIl. There is a polar granule. Sporocystsare elongated and ovoid averaging 11 by 6 millimicron in size with a Stieda .body and containing a sporocysts residuum.First generation schizonts develop throughout the intestine, mainly in the crypt of Lieberktihn but also in the muscularis muscosae, lamina propria and epithelial cells above the host nucleus. About 1.4 morozoites are produced.Second generations also develop throughout the' intestine, mainly in the 'lamina propria, below the host nucleus. About 12 morozoites are produced.Gametoytes are most numerous in the mid-intestine, large intestine and cecum and are mainly in the lamina propria.Pathogenicity was mild. Diarrhea and mucoid edema were the only clinical signs observed and the infection was self-limiting, ending after about 20 days.